The Physical Analyze of Local Grass - Suhartati, FM; Suryapratama, W; Rahayu, S (ANIMAL PRODUCTION, 2004)
A research has been conducted to analyze physical characteristics of local grass. The aimed of this research was to observe grass physical characteristics, which are bulkiness, water regain capacity and water solubility. Also to observe correlation of water regain capacity to dry matter and organic matter digestibility as well as its degradation rate during 0, 12, 18 and 24 h incubation, in sacco, using 2 fistulae cows.  Five local grass were tested in this research, which are field grass, elephant grass, brachiaria grass, king grass and setaria. Fistulae cows consumed forages and concentrates with ratio of 70:30, minimum protein level of 12% and minimum TDN of 60%. Physical characteristics data that obtained then analyzed using analysis of variance. Furthermore, honestly significant different was also performed. Dry matter and organic matter digestibility data that obtained were analyzed with regression of physical characteristics.  Result showed that brachiaria grass has poor water regain capacity and water solubility.  There are positive linear correlation between water regains capacity with dry matter and organic matter digestibility. (Animal Production 6(1): 37-42 (2004) Key Words: Bulkiness, Water Regain Capacity, Water Solubility, Dry Matter and Organic Matter Digestibility